VOLUME PLASMA DAN FAKTOR VIII DALAM KRIOPRESIPITAT - Dian Widyaningrum; Purwanto AP; Julia Setyati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Blood product such as cryoprecipitate required a quality control. This includes development, implementation and the standard operating procedures use of each step of the process in the production of cryoprecipitated substance to ensure that the produced product contains a minimum of 80 international units (IU) of factor VIII. Cryoprecipitation is prepared from fresh frozen plasma that thawed and centrifuge by immediate spinning the excess plasma which then removed and leaving approximately 40ml which deposit 10 mL cryoprecipitate. One unit of cryoprecipitate contain 70–80 IU/unit factor VIII, ≥100 mg/unit von Willebrand factor, fibrinogen 5–10 mg/dL. The levels of factor VIII and von Willebrand factor (VWF) lowered in individuals with blood group O compared to individuals groups with non-O blood. This research is aimed to investigate whether plasma volume are correlated with the levels of factor VIII in cryoprecipitation. In this study purposive sampling is done in which 25 bags of cryoprecipitate materials (was storage for 11 months) from all types of blood group which were taken from storage, thawed, weighed and the plasma volume measured. Factor VIII was measured by coagulometric method. The researcher used Spearman correlation test to analyze the product, with significance degree p<0.05 and confidence interval 95%. In this study it is found plasma volume which was not related to the factor VIII level in cryoprecipitattion substance (p=0.585). Mean plasma volume of the cryoprecipitated matter was 56 mL, mean factor VIII was 83.3UI. Highest factor VIII level was 160.6 UI of cryoprecipitated blood group AB and lowest factor VIII level was 21.3 UI of cryoprecipitated blood group A.